1993
DOI: 10.1056/nejm199309093291105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Fish Oil on Renal Function and Rejection in Cyclosporine-Treated Recipients of Renal Transplants

Abstract: The daily administration of 6 g of fish oil during the first postoperative year has a beneficial effect on renal hemodynamics and blood pressure in renal-transplant recipients treated with cyclosporine. Although the fish-oil group had significantly fewer rejection episodes than the control group, graft survival at one year was not significantly better in the fish-oil group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(68 citation statements)
references
References 24 publications
5
61
0
2
Order By: Relevance
“…Another strategy reported is dietary supplementation with fish oil. van der Heide et al (68) observed that recipients of a primary cadaveric kidney transplant who were treated with CsA and who ingested fish oil daily during the first postoperative year had higher glomerular filtration rate and renal plasma flow than those not ingesting fish oil. However, a more recent randomized, double-blind, placebo-controlled in transplant patients taking CsA showed no beneficial effect of fish oil on glomerular filtration rate and renal plasma flow, as well as on renal histopathology.…”
Section: Invited Reviewmentioning
confidence: 99%
“…Another strategy reported is dietary supplementation with fish oil. van der Heide et al (68) observed that recipients of a primary cadaveric kidney transplant who were treated with CsA and who ingested fish oil daily during the first postoperative year had higher glomerular filtration rate and renal plasma flow than those not ingesting fish oil. However, a more recent randomized, double-blind, placebo-controlled in transplant patients taking CsA showed no beneficial effect of fish oil on glomerular filtration rate and renal plasma flow, as well as on renal histopathology.…”
Section: Invited Reviewmentioning
confidence: 99%
“…Therefore, these agents (particularly the n-3 series) have found clinical applications in the treatment of various inflammatory diseases such as rheumatoid arthritis and Crohn's disease relapses (33,35,36) and as immunosuppressive agents (32). Despite the broad clinical use of PUFAs, the mechanism of PUFA-induced T cell inhibition had not been elucidated.…”
Section: -Bromopalmitate Inhibits Fyn Fatty Acylation and Signaling mentioning
confidence: 99%
“…Polyunsaturated fatty acids (PUFAs), particularly the n-3 series, are used clinically as immunosuppressive agents (32) and in the treatment of various inflammatory diseases (33)(34)(35)(36). Recently, it was reported that PUFAs inhibit T cell signal transduction by displacing Fyn and Lck from the DRMs (37).…”
mentioning
confidence: 99%
“…Other studies did not report such an effect for fish oil in either rat or rabbit models of cardiac transplantation (55,56). On the other hand, the benefits of fish oil in the prevention of chronic rejection were reported in kidney transplant recipients (21). Regardless, the lower number of rejection The distribution of rejection grades are not significantly (P ϭ 0.241) different among groups according to the 2 -test analysis.…”
Section: Discussionmentioning
confidence: 92%